Hepatocellular carcinoma arising from hepatic adenoma in a young woman. Issue 9 (27th May 2020) - Yacoub, Haythem; Kchir, Hela; Cherif, Dhouha; Hassine, Hajer; Haouet, Slim; Ayari, Asma; Mizouni, Habiba; Mannai, Saber; Khalfallah, Mohamed Tahar; Maamouri, Nadia
Abstract: Hepatocellular carcinoma (HCC) arising from hepatic adenoma is an infrequent situation. Only a few cases were reported in the literature. We present a rare case of hepatocellular carcinoma arising from HA in a young woman with no medication history of oral contraceptives. Surgical resection is the only available treatment. Abstract : Hepatocellular carcinoma (HCC) arising from hepatic adenoma is an infrequent situation. Only a few cases were reported in the literature. We present a rare case of hepatocellular carcinoma arising from HA in a young woman with no medication history of oral contraceptives. Surgical resection is the only available treatment.